Kapital i kulturni hegemonizam: kratki historijski pregled »stranog elementa« u norveškom društvu - Chepulis, Rita L.; Oslo, Norway (Institute for Migration and Ethnic Studies, 1985)
Ovaj rad obrađuje s povijesnog gledišta neke socioekonomske aspekte položaja indigenih Samija (Laponaca) i stranih radnika u Norveškoj. Raspravlja se prvo o implikacijama pojava poput »homogenog društva« a zatim, upotrebom Edward Saidovog pojma »fleksibilne pozicije superiornosti«, analizira se odnos stranaca prema dominantnom norveškom društvu. Rad posebno pokušava istaknuti kako su u povijesti i danas na razne načine kombinirani ekonomski interesi i hegemonistički stavovi »zapadne« kulture da bi se opravdalo: a) proizvoljno određivanje »strane« i »migrantske« kategorije, b) unutrašnja kolonizacija i politika ponorveživanja i c) kontrola i isključenje određenih stranih grupa iz društva. The paper examines from a historical perspective, certain socio-economic aspects of the indigenous Sami and foreign workers' situation in Norway. The discussion deals first with the implications of concepts such as “homogeneous society” and second, using Edward Said's notion of “flexible positional superiority”, analyzes the foreigner's relationship to the dominant Norwegian society. In particular, the paper attempts to show that a combination of both economic interests and Western cultural hegemonistic attitudes have been used, historically and actually, in various ways to legitimize: a) arbitrary designations of “foreign” or “migrant” categories; b) internal colonialism and a policy of Norwegianization; and c) control and exclusion of particular foreign groups from the society.